THE ANALYTICAL DYNAMIC MODEL OF THE STRUCTURE OF THE INFORMATION SYSTEM CONDITION (Web of Teachers: Inderscience Research, 2025)
The article describes the mathematical expression of the dynamic characteristics of the transmission properties of the object represented by the line he selects automatic control systems using real input and output variables and output variables of abstract types kosh represented by the differential equation.